Computer dynamics to evaluate blood flow through the modified Blalock-Taussig shunt - Sant'Anna,João Ricardo M. (2003)
OBJECTIVES: To study the influence of geometric factors upon the function of modified Blalock-Taussig anastomoses (mBT) using a computational dynamic code based upon the method of finite elements. METHODS: The mBT operation, performed in 10 patients, was graphically reconstructed to create a parametric 3-dimensional geometric model. Using Streamline Upwind/Petrov-Galerkin approximations, blood flow and distribution were evaluated in different diameters of subclavian arteries and polytetrafluoroethylene grafts (PTFE) and angles of proximal anastomoses. RESULTS: The percentage of blood flow derived through the PTFE grows as its diameter increases in relation to subclavian artery diameter. Variations in the PTFE diameter do not interfere with pulmonary artery flow distribution. An angle of 110º in proximal anastomoses results in a high percentage of blood derivation to the graft, while angles of 30º, 60ºand 90º present with almost similar flow rates. However, angles of 30º and 110º produce an excessive flow to one of the pulmonary arteries, in detriment of the other. Peak pressure in the PTFE is affected by the proximal angle of anastomosis, with 30º resulting in higher and 110º in lower values. As the angle increases, the region of higher pressure shifts from the PTFE to subclavian artery. CONCLUSION: In the experimental model, percentage of flow derived in the PTFE is directly related to the diameter of the graft. The ratio between the diameters of subclavian artery and graft is an important regulator of flow deviation to the anastomosis. Angles of the anastomosis between the subclavian artery and the PTFE of 60º to 90º result in favorable pulmonary artery flow distribution and the location of the peak pressure.